Comprehensive characterization of human alveolar epithelial cells cultured for 28 days at the air-liquid interface - Ikuya Tanabe; Shinkichi Ishikawa (Scientific Reports)
Abstract Lung epithelia are exposed to various substances in the atmosphere through breathing. To investigate the mechanisms and treatments for respiratory diseases caused by these substances, robust in vitro lung epithelial models are essential. This study aimed to develop an in vitro alveolar epithelial model using primary human pulmonary alveolar epithelial cells (HPAEpiCs). HPAEpiCs were cultured at an air-liquid interface (ALI) for 28 days in a medium supplemented with three small molecules: Y-27632, A-83-01, and CHIR99021. The characteristics of the ALI-cultured cells were then analyzed. Immunostaining revealed that many cells expressed alveolar type 2 (AT2) cell markers, such as surfactant protein B and prosurfactant protein C. Single-cell gene expression analysis further confirmed that the majority of the cells expressed genes reported to be highly expressed in AT2 cells. The apical surface of the ALI-cultured HPAEpiCs was covered with a liquid containing a variety of lipids and proteins known to be present in lung surfactant in vivo. Our data demonstrate that 28 days of ALI culture promoted the differentiation of HPAEpiCs into AT2 cells capable of secreting lung surfactant components. This ALI culture model containing differentiated AT2 cells could be valuable for investigating the mechanisms and treatments for respiratory diseases.